2015
DOI: 10.1016/j.ipej.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Bundle-branch reentry ventricular tachycardia after transcatheter aortic valve replacement

Abstract: An 83-year-old male suffering from severe symptomatic aortic valve stenosis received an implant of a biological aortic prosthesis through the femoral artery without complications. Seven days after dischargement he experienced a syncope. The patient was wearing an ECG holter monitor that day, which showed a wide QRS complex tachycardia of 300 beats per minute. The electrophysiological study revealed a bundle-branch reentry ventricular tachycardia as the cause of the syncope. Radio-frequency was applied on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Possible mechanisms of VTa in patients with VHD could be multifactorial. VT caused by bundle branch reentry (BBR) has been reported in patients with VHD, both before and after valve replacement (10)(11)(12)(13)(14). Narasimhan et al demonstrated that BBR accounts for 30% of sustained monomorphic VT cases after valve surgery (15).…”
Section: Ventricular Tachyarrhythmias In Patients Undergoing Surgical Valve Replacementmentioning
confidence: 99%
“…Possible mechanisms of VTa in patients with VHD could be multifactorial. VT caused by bundle branch reentry (BBR) has been reported in patients with VHD, both before and after valve replacement (10)(11)(12)(13)(14). Narasimhan et al demonstrated that BBR accounts for 30% of sustained monomorphic VT cases after valve surgery (15).…”
Section: Ventricular Tachyarrhythmias In Patients Undergoing Surgical Valve Replacementmentioning
confidence: 99%